2018
DOI: 10.1177/0890117118811754
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Implications of Google Searches for Sunscreen, Sunburn, Skin Cancer, and Melanoma in the United States

Abstract: Purpose: Google Trends (GT) offers insights into public interests and behaviors and holds potential for guiding public health campaigns. We evaluated trends in US searches for sunscreen, sunburn, skin cancer, and melanoma and their relationships with melanoma outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…The worldwide search interest in “sunscreen” has been generally increasing since 2008 with a waning trend for the search term “tanning bed.” In the United States of America, Google Trends® found that melanoma incidence was positively associated with searches for “sunscreen” and “sunburn” and negatively associated with “skin cancer” searches. Mortality was negatively associated with searches for “sunscreen.” Although there was an increase in searches for “sunscreen” and “sunburn” over time, there were less searches for “melanoma” and “skin cancer.” Researchers also found that the American public developed increasing interest in the search term “Mohs surgery” since 2004, in tandem with the positive trends reported for the terms “basal cell carcinoma” and “squamous cell carcinoma,” mirroring the increasing number of such procedures performed in the United States …”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The worldwide search interest in “sunscreen” has been generally increasing since 2008 with a waning trend for the search term “tanning bed.” In the United States of America, Google Trends® found that melanoma incidence was positively associated with searches for “sunscreen” and “sunburn” and negatively associated with “skin cancer” searches. Mortality was negatively associated with searches for “sunscreen.” Although there was an increase in searches for “sunscreen” and “sunburn” over time, there were less searches for “melanoma” and “skin cancer.” Researchers also found that the American public developed increasing interest in the search term “Mohs surgery” since 2004, in tandem with the positive trends reported for the terms “basal cell carcinoma” and “squamous cell carcinoma,” mirroring the increasing number of such procedures performed in the United States …”
Section: Introductionmentioning
confidence: 95%
“…Although there was an increase in searches for "sunscreen" and "sunburn" over time, there were less searches for "melanoma" and "skin cancer." 13 Researchers also found that the American public developed increasing interest in the search term "Mohs surgery" since 2004, in tandem with the positive trends reported for the terms "basal cell carcinoma" and "squamous cell carcinoma," mirroring the increasing number of such procedures performed in the United States. 11 Using data obtained from Google Trends®, we aimed to examine the geographic and temporal trends in Internet search interest for terms related to sun protection and skin cancers in three neighboring countries in South-East Asia, namely Malaysia, Singapore, and Indonesia.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some researchers studied mental health [53] and depression [54] queries. Other topics studied using GT data are skin cancer [55], sunscreen use [56], sunburn [57], seasonality of bruxism [58], multiple sclerosis [59], cancer [60], stroke [61], HIV [62], lupus [63], norovirus [64], sepsis [65], pertussis [66], epistaxis [67], plague [68], rheumatoid arthritis [69], and prostate cancer [70]. In terms of general population behavior, research was done using GT data on pharmaceutical data [71], vaccinations [72], movement disorders [73], digital epidemiology [74], kidney stone surgery [75], foot and ankle pain [76], knee injuries [77], osteoarthritis [78], seasonality of cellulitis [79], tracking influenza epidemics using climate data [80], palliative care [81], cosmetic body procedures [82], and anesthesia [83].…”
Section: Introductionmentioning
confidence: 99%